Advances in doubled haploid technology for rice breeding: mechanisms, applications, and future perspectives - Lin, Yiling; Mao, Fangming; Huang, Yuheng; Huang, Derun; Wang, Kejian; Yan, Song; Liu, Chaolei (Frontiers in Plant Science, 2026)
Production of homozygous inbred lines is crucial in rice breeding programs. Doubled haploid (DH) technology enables the efficient development of pure lines and significantly shortens the breeding cycle compared to conventional methods. This review summarizes recent advances in the four key steps of DH technology mediated by haploid inducers in rice: (1) exploration of haploid induction genes and development of high-efficiency haploid inducers, (2) rapid identification of haploids using molecular and morphological markers, (3) chromosome doubling of haploid plants through colchicine treatment, and (4) application of DH technology in rice breeding. Furthermore, current challenges and issues associated with each step are discussed. With ongoing advancements and the resolution of existing limitations, DH technology based on haploid inducers is anticipated to become a fundamental and widely adopted tool in rice breeding.